2023
DOI: 10.1088/1361-6439/ace05e
|View full text |Cite
|
Sign up to set email alerts
|

Thermally/mechanically robust anodic aluminum oxide (AAO) microheater platform for low power chemoresistive gas sensor

Abstract: The semiconductor metal oxide (SMO) gas sensors are getting high attention owing to their high sensitivities and fast responses. They require high temperature for the reaction with target gases, and suspended silicon membrane microheaters are typically used to reduce the heating power consumption. However, they have low durability for long-term uses, and high probability of fracture by thermal stress or mechanical impact. In this study, as an alternative to the silicon membrane microheater, anodic aluminum oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The mechanical stability of the multilayer membrane structure was tested, and it was found that the center of the microheater deflected more than a few micrometers after heating the microheater plate to a temperature of 350 K. When the microheater was heated to 550 K, the amplitude of the center of the microheater exceeded 30–40 μm. Byeongju Lee et al [ 20 ] prepared an anodized aluminum oxide-based microheater that fabricated a bridge structure with the same thickness as the substrate using the etching mechanism of the anodized aluminum oxide substrate. Because the heating platform uses the entire thickness of the substrate instead of a microscale membrane, the microheater platform has exceptional mechanical and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical stability of the multilayer membrane structure was tested, and it was found that the center of the microheater deflected more than a few micrometers after heating the microheater plate to a temperature of 350 K. When the microheater was heated to 550 K, the amplitude of the center of the microheater exceeded 30–40 μm. Byeongju Lee et al [ 20 ] prepared an anodized aluminum oxide-based microheater that fabricated a bridge structure with the same thickness as the substrate using the etching mechanism of the anodized aluminum oxide substrate. Because the heating platform uses the entire thickness of the substrate instead of a microscale membrane, the microheater platform has exceptional mechanical and thermal stability.…”
Section: Introductionmentioning
confidence: 99%